Lastik Agregali Betonların Yük Altındaki Gerilme Davranışlarının İncelenmesi - Emiroğlu, Mehmet; Aydın, Murat; Yıldız, Servet (My University, 2011)
There have been various studies aboutevaluation of waste vehicle tires as aggegate in conc rete. Composite material called rubberized concrete produced for the purpose of both recycling of the wastes and achieving more flexible concretes. The aim of the wastes and achieving more flexible concretes. The aim of this study is investigate the stress behavior of this composite obtained using a combination of flexible and rigid materials with finite element analysis.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Concrete; rubberized; Finite element analysis